Computer Ethics and Professional Responsibility - Bynum, Terrell Ward; Rogerson, Simon (Blackwell Pub., 2004)
Keywords: Electronic data processing; Moral and ethical aspects; dept.phi; faculty_collection

The "Backwards, Forwards and Sideways" Changes of Ict: Ethicomp 2010: Proceedings of the Eleventh International Conference - International Conference on the Social and Ethical Impacts of Information and Communication Technologies (11th : Universitat Rovira i Virgili, Tarragona; Arias-Olive, Mario; Bynum, Terrell Ward; Rogerson, Simon; Torres-Coronas, Teresa; Centre for Computing and Social Responsibility (Universitat Rovira i Virgili, 2010)
"The purpose of this series is to provide an inclusive European forum for discussing the ethical and social issues associated with the development and application of Information and Communication Technology (ICT). The conferences are held every 18 months."--Introduction.
Keywords: Congresses; Congresses; Information technology; Information technology; Moral and ethical aspects; Professional ethics; dept.phi; faculty_collection